Interannual variability in the Saharan dust source activation—Toward understanding the differences between 2007 and 2008. Issue 9 (7th May 2016) - Wagner, Robert; Schepanski, Kerstin; Heinold, Bernd; Tegen, Ina
Abstract: The activation of Saharan dust sources is characterized by a diurnal and seasonal cycle and a strong interannual variability. Here reasons for the still unclear interannual changes were investigated using the example of 2007 and 2008, which were years with a clear difference in the number of observed dust source activation (DSA) events. A detailed analysis of dust images derived from satellite observations showed that a sudden increase of DSA at the turn of the year 2007/2008 spreads within some months from eastern to northwestern parts of North Africa. The DSA remains on this significantly enhanced level during the whole year 2008. An examination of regional model and global reanalysis results, and satellite data, was performed to identify drivers for the different DSA patterns, which revealed that many individual factors contributed to the enhanced DSA in 2008. This includes changes in the Sahel rainfall distribution, the wind field over North Africa, differences in the strength of the West African Heat Low, and the occurrence of cold surges propagating from the Mediterranean into the Sahara. The determining factor of at least some of these influences appears to be differences in sea surface temperatures, especially in the tropical Indian and Pacific Oceans, and in the Mediterranean Sea, affecting the large‐scale and local atmospheric circulation patterns and finally fostering Saharan DSA. The activation of alluvial sediments as dust sources after heavy rainfalls in 2007 also plays an important role. Its contribution to the enhanced DSA remains part of further research activity. Key Points: Investigation of multiyear Saharan DSA showed a significant increased activity in 2008 Tropical SST variations and their atmospheric response appear to trigger this increase Regional circulation pattern and precipitation changes contribute to it